2013
DOI: 10.1098/rspb.2013.0762
|View full text |Cite
|
Sign up to set email alerts
|

Too risky to settle: avian community structure changes in response to perceived predation risk on adults and offspring

Abstract: Predation risk is widely hypothesized as an important force structuring communities, but this potential force is rarely tested experimentally, particularly in terrestrial vertebrate communities. How animals respond to predation risk is generally considered predictable from species life-history and natural-history traits, but rigorous tests of these predictions remain scarce. We report on a large-scale playback experiment with a forest bird community that addresses two questions: (i) does perceived predation ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…However, preliminary spatial analyses failed (p > 0.60) to support a relationship between mouse activity clusters and veery or ovenbird nest success (Emmering ). In addition, based on rodent removal studies, Brunner et al () found no experimental evidence for competition among rodents (mice, chipmunks and squirrels) at our site, concluding: ‘with only weak or nonexistent competition among these three common rodent species, we expect their patterns of habitat occupancy and population dynamics to be largely independent of one another’. For these reasons, we focus our present analyses on chipmunks only.…”
Section: Methodsmentioning
confidence: 61%
“…However, preliminary spatial analyses failed (p > 0.60) to support a relationship between mouse activity clusters and veery or ovenbird nest success (Emmering ). In addition, based on rodent removal studies, Brunner et al () found no experimental evidence for competition among rodents (mice, chipmunks and squirrels) at our site, concluding: ‘with only weak or nonexistent competition among these three common rodent species, we expect their patterns of habitat occupancy and population dynamics to be largely independent of one another’. For these reasons, we focus our present analyses on chipmunks only.…”
Section: Methodsmentioning
confidence: 61%
“…Additionally, non-lethal effects on prey behaviour could lower bird densities in noisy areas. That is, if prey perception of risk was elevated by noise [18] because of the lack of social (this study) or personally collected information concerning lethal risks, then prey might selectively avoid such areas [19]. In sum, either a loss of antipredator information or disruption of appropriate responses to alarm calls could lead to decreased density of prey birds via increased predation success or prey avoidance.…”
Section: Discussionmentioning
confidence: 88%
“…By using a silent control, we avoided the potential problems mentioned above, but on the other hand we cannot rule out the possibility that the playback (increased vocal activity in a site) or merely the presence of a playback machine affected the behavior of individuals in the playback sites. However, taking into account the scale of our experiment (average patch size ¼ 8 ha), any such effects are most likely negligible-and probably far weaker than the potential effects of, for example, heterospecific attraction or avoidance had the playback control been used instead of the silent control (for similar arguments, see Farrell et al 2012, Hua et al 2013. Similar experimental designs using silent controls have been applied extensively in studies of avian habitat selection (e.g., Hahn and Silverman 2006, Farrell et al 2012, Hua et al 2013, Ware et al 2015.…”
Section: Methodsmentioning
confidence: 99%
“…However, taking into account the scale of our experiment (average patch size ¼ 8 ha), any such effects are most likely negligible-and probably far weaker than the potential effects of, for example, heterospecific attraction or avoidance had the playback control been used instead of the silent control (for similar arguments, see Farrell et al 2012, Hua et al 2013. Similar experimental designs using silent controls have been applied extensively in studies of avian habitat selection (e.g., Hahn and Silverman 2006, Farrell et al 2012, Hua et al 2013, Ware et al 2015. Nonetheless, if the increased vocal activity due to the playback-or the mere presence of a playback machinerepels birds, one could expect a consistent negative effect on bird abundance across sites and species, irrespective of the latter's status as cuckoo hosts.…”
Section: Methodsmentioning
confidence: 99%